The lost heiress - White, Roseanna M., 1982- (2015)
"In 1910 Edwardian England, a British-born young heiress raised in the palace of Monaco comes to Yorkshire, where mystery and tragedy threaten her very existence"--
Keywords: Romantic suspense fiction